Cryptocurrency as a Tool of Crime: An Intersectional Study of Technology, Law, and Criminology - Syamsul Hidayat; Atika Zahra Nirmala; Nunung Rahmania (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Cryptocurrency has developed as a rapidly growing financial innovation, but it also gives rise to serious challenges, particularly the increase in crimes such as money laundering. Its decentralized, pseudonymous, and borderless characteristics make it difficult for law enforcement authorities to trace illegal transactions and highlight a gap between technological advancement and regulatory readiness. Based on this issue, this study raises the following questions: (1) how is cryptocurrency used in money laundering mechanisms, (2) how is it regulated in Indonesia, and (3) how do technology, law, and criminology intersect in addressing this issue. This study aims to analyze these three aspects comprehensively. This research employs a normative juridical method with statutory, conceptual, and case approaches, utilizing primary and secondary legal materials obtained through library research and analyzed using a descriptive qualitative method. The findings show that cryptocurrency is used in money laundering through the stages of placement, layering, and integration, with increasingly complex methods based on digital technology. Addressing this issue requires an interdisciplinary synergy, where technologies such as blockchain forensics and artificial intelligence assist in tracing transactions, law provides the normative framework and enforcement mechanisms, and criminology explains offender motives and behavioral patterns. However, the regulatory framework in Indonesia remains partial and not fully adaptive to the development of digital assets. The academic contribution of this study lies in strengthening the interdisciplinary approach as a basis for more adaptive policymaking, as well as providing recommendations for regulatory improvement, enhancing law enforcement capacity, and developing more effective preventive strategies in addressing cryptocurrency-based money laundering.